Spectral Quality Affects Morphogenesis on Anthurium Plantlet during In Vitro Culture - Kurniawan Budiarto (AGRIVITA, Journal of Agricultural Science, 2010)
This paper elucidates the effects of LEDs spectral on callus induction, proliferation and shoot development of anthurium plantlet derived from leaf explants. The research was conducted at the Ornamental Research Station, Fukuyama, Japan from January to August 2008. Three experimental series were designed to determine the effects of LED-based spectral compositions i.e. 100% red, 75% red + 25% blue, 50% red + 50% blue, 25% red + 75% blue and 100% blue LEDs on morphogenetic process of callus formation derived from leaf explants up to plantlet formation on two anthurium cultivars, Violeta and Pink Lady. The results showed no differences among cultivars tested but interaction of factors studied were found in all parameters observed. LEDs spectral gave significant influence on the morphogenetic processes from callus induction to complete plantlet formation. Progressive initial callus was promoted with the decrease of blue LEDs portion. Conversely, to proliferate globose to torpedo callus formation, more blue light was required than red LEDs. During shoot induction and formation, hastened shoot initiation and number of shoots were achieved in higher blue LEDs portions, but not in root formations. Keywords : Anthurium, LEDs spectrals, morpho-genesis, plantlet, in vitro